1988
DOI: 10.1080/01932698808943999
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Free Microemulsions

Abstract: Ternary and Pseudo-ternary phase behavior of the system water/hexadecane/dioctyl sodium sulfosuccinate (DSS)/sorbitan 1aurate has been determined.The mi croemuls i on regi on of thi s alcohol-free system has potential for use as a pharmaceutical topical vehicle.A 1/1 weight ratio of sorbitan laurate:DSS (60:40)/hexadecane can solubil ize up to 55% water, while sobitan 1aurate: DSS ratios larger than 70/30 show dramat i cally decreased water solubilization at equivalent hexadecane concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…This indicated that the w/o system was converted to the o/w system through a bicontinuous state. Such a behavior was reported earlier for polyoxyethylene [10] oleyl alcohol (Brij-97)/butanol/dodecane/water [58]; SDS/propanol/cyclohexane/water [59]; and CTAB/1-propanol/cyclohexane/water [60] systems. O/w systems have been observed to have viscosity values higher than those of the w/o systems.…”
Section: Viscosity Studymentioning
confidence: 54%
See 1 more Smart Citation
“…This indicated that the w/o system was converted to the o/w system through a bicontinuous state. Such a behavior was reported earlier for polyoxyethylene [10] oleyl alcohol (Brij-97)/butanol/dodecane/water [58]; SDS/propanol/cyclohexane/water [59]; and CTAB/1-propanol/cyclohexane/water [60] systems. O/w systems have been observed to have viscosity values higher than those of the w/o systems.…”
Section: Viscosity Studymentioning
confidence: 54%
“…Owing to their diphilic nature, surfactants distribute their head and tail parts to the corresponding pothe system; (iii) reduce interfacial tension; (iv) increase the fluidity of the interface and thereby increasing the entropy of the system; (v) increase the mobility of the hydrocarbon tail and allow greater penetration of the oil into this region; and (vi) influence the solubility properties of the aqueous and oleic phases due to its partitioning between the phases. Several attempts to substitute traditional cosurfactants with other components [9][10][11][12][13][14], for example, nonionic surfactants, alkanoic acids, alkanediols, amines, aldehydes, ketones, butyl lactate, and oleic acid, have been carried out from the viewpoint of suitable applications of microemulsions. The roles of cosolvents and additives in the preparation of microemulsions are also reported [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the area of microemulsion region is considerably large since 1-propanol acts as a co-surfactant and interacts with the surfactant monolayer to increase the flexibility of the interfacial film. Microemulsions are formed spontaneously when their components come together [12]. The order of mixing of various components is not expected to influence the formation of microemulsions if the system is indeed thermodynamically stable.…”
Section: Refractive Index Measurementsmentioning
confidence: 99%
“…There was no phase separation or precipitation which indicates the non ionic surfactants used were stable to change in pH and the concentration of electrolyte. 46 This is necessary for stable emulsion system as it gets in contact with various physiological fluids in the system. …”
Section: Dilution and Ph Effectmentioning
confidence: 99%